Estudio para la optimización del proceso de recogimiento de malla expandida del área de trefilados de la empresa acería del ecuador (Adelca) en el cantón Mejía, provincia de Pichincha en el período 2012 - Carranza Camacho, Luis Carlos (2013)
This research project was developed in order to conduct a study to optimize the process of recollection expanded mesh (finished product), seeing the need to improve productivity through time and motion study in the area of the plant expanded mesh of industrial enterprise drawn “ADELCA C.A”. The same is located at Mejia Canton, Pichincha Province, Alóag Parish. By identifying the problem through a diagnosis of the current process on their operators were able to estimate that the production line has expanded mesh problems at the end of the process of recollection mesh. This action is done in proper working conditions for the proper development of the worker. This determines low levels of productivity. My proposal is to design a mesh collector automatically, which do the work automatically in order to improve productivity and thus avoid injuries in your operators and managed to increase production to 50% by reducing production costs and improving the presentation of the finished product. The research is descriptive; whose technique was field observation. With this proposal it had lowered production time optimizing resources, eliminating unnecessary tasks and improving others, however much loss of time in the process of expanded mesh recollection was because there was no automated process to replace the manual process , overcoming these drawbacks are managed to increase their productivity.